2009
DOI: 10.1186/1477-7819-7-31
|View full text |Cite
|
Sign up to set email alerts
|

A giant hemolymphangioma of the pancreas in a 20-year-old girl: a report of one case and review of the literature

Abstract: Background: Hemolymphangioma of the pancreas is a very rare benign tumor. There were only six reports of this disease until December 2008. Herein, we report a case of giant hemolymphangioma of the pancreas in a 20-year-old girl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 3 publications
(4 reference statements)
1
27
0
Order By: Relevance
“… 11 The abnormal venolymphatic communication between the dysembryoplastic vascular tissue and blood circulation could be the reason for the formation of this tumor, as well as the obstruction of lymph drainage or lymphatic damage. 7 Most studies consider hemolymphangioma as a benign tumor due to its good prognosis, but some studies found that it can invade the adjacent structures, 12 13 the same as our case. Diffuse or giant celiac hemolymphangioma is very rare and even rarer is the involvement of the spleen.…”
Section: Discussionsupporting
confidence: 60%
“… 11 The abnormal venolymphatic communication between the dysembryoplastic vascular tissue and blood circulation could be the reason for the formation of this tumor, as well as the obstruction of lymph drainage or lymphatic damage. 7 Most studies consider hemolymphangioma as a benign tumor due to its good prognosis, but some studies found that it can invade the adjacent structures, 12 13 the same as our case. Diffuse or giant celiac hemolymphangioma is very rare and even rarer is the involvement of the spleen.…”
Section: Discussionsupporting
confidence: 60%
“…Microscopically, the tumor consists of abnormal lymphatic and blood vessels with polycystic spaces. These cysts have connective septa covered by endothelium (1). The tumor is possibly surrounded by adipose or interstitial fibrous tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Hemolymphangiomas have been found in the pancreas, at the extremities, in the mediastinum, pericardium and on the tongue, as well as in the orbit, esophagus, retroperitoneally, adrenally, cervically, thoracically, hepatically and in the spleen (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). In addition, there are also reports of hemolymphangiomas in the skin, throat, stomach and scrotum in Chinese literature (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Hemolymphangioma is very rare, and few cases occurring in the rectum, spleen, pancreas, liver have been reported [1][2][3][4][5][6]. Hemolymphangioma often arises from congenital malformation of vascular and lymphatic system.…”
Section: Introductionmentioning
confidence: 99%